Myeloma multiplex with pulmonary dissemination - Terzić, Brankica; Maksić, Djoko; Škuletić, Vesna; Pilčević, Dejan; Mijušković, Mirjana; Čukić, Zoran; Obrenčević, Katarina; Petrović, Marijana; Tadić - Pilčević, Jelena; Petrović, Milica (Vojnosanitetski pregled, 2014)
Introduction. Multiple myeloma is a hemathological malignancy characterized by the clonal proliferation of plasma cells in the bone the marrow. Extramedullary dissemination of multiple myeloma is uncommon. In several cases only, the multiple myeloma malignant plasma cells had diseminated to the lung parenchyma. Case report. We presented a case of multiple myeloma with lung plasmacytoma, in a 79-year-old patient, hospitalized for febrility and infiltrative mass in the right lung. Two months before the patient was admitted, because of developing terminal renal failure, hemodialysis treatment had started three times a week. Since then, the patient was oliguric, but because of febrility and hemoptysis that appeared, at first he was treated with dual antibiotic therapy which resulted in temporary improvement of his general condition, but pleural effusion remained. After thoracocentesis, followed by myelogram, the multiple myeloma diagnosis was established. Conclusion. In patients of middle and older age, with general weakness, exhaustion, loss of weight, renal failure which progresses to the end stage rapidly, if symptoms of respiratory tract occur, consider this uncommon disease – extramedullary dissemination of multiple myeloma.